2020
DOI: 10.1590/s0100-83582020380100026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetic Variation and Spread of Phalaris minor Resistant to ACCase Inhibiting Herbicides in Iran

Abstract: Littleseed canarygrass (Phalaris minor) is the second most serious and problematic grass weed in wheat fields in Iran, and has developed resistance to ACCase inhibiting herbicides. Inter-simple sequence repeat (ISSR) analysis was used to assess genetic variation between and within ACCase inhibitor-resistant and susceptible P. minor populations in Iran and to determine the origin of resistance and its dispersal. Sixteen P. minor populations from different regions in Iran were analysed using seven primers. Genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, Phalaris spp. are highly competitive plants with high seed production [ 6 , 7 , 8 ]; therefore, managing these grasses is essential to avoid compromising crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Phalaris spp. are highly competitive plants with high seed production [ 6 , 7 , 8 ]; therefore, managing these grasses is essential to avoid compromising crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…grapevines reported that day length could act as an abiotic factor for alteration of protein patterns and can lead to a different expression pattern of agronomic characteristics in plants. Gherekhloo et al ( 2020 ) studied Phalaris minor populations and reported a high genetic similarity among the populations in different regions. Bahraminrjad and Mohammadinejad (2013) reported that different cultivation conditions influenced the agro-morphological traits of cumin ecotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the experiments confirm the substitution of Ile-1781 with Leu in all resistant biotypes of L. rigidum (R 1 , R 2 , R 3 and R 4 ) (Table 10). Changes in the amino acids of the carboxyl transferase (CT) domain is considered to be an obstacle to the binding of ACCase inhibitors in this domain and ultimately causes TSR resistance (Hassanpour-bourkheili et al 2021;Gherekhloo et al, 2020). In general, researchers believe that the common cause of resistance to ACCase inhibitors such as APP, CHD and PPZ is the mutation at point 1781, which is considered the most frequent mutation in this domain (Golmohammadzadeh et al, 2020).…”
Section: Accase Gene Sequencingmentioning
confidence: 99%
“…ACCase inhibitors are categorized into aryloxyphenoxypropionates (APP1), aryloxyphenoxypropionates (APP2), cyclohexanediones (CHD) and phenylpyrazoline (PPZ) chemical classes (Hassanpourbourkheili et al, 2021). ACCase inhibitors disrupt the activity of the ACCase enzyme in the plastid of monocots plants, while these herbicides do not affect the heteromeric ACCase enzyme present in dicotyledons (Hassanpour-bourkheili et al 2021; Gherekhloo et al, 2021;Gherekhloo et al, 2020). One hundred seventy species (105 dicotyledonous and 65 monocotyledonous species) are reported to be resistant to acetolactate synthase (ALS) inhibitors (Heap, 2022).…”
Section: Introductionmentioning
confidence: 99%